Sosialisasi Dan Edukasi Konservasi Penyu Di Pantai Sodong Nagaraja Cilacap “Penyu Sahabat Kita” : Pengabdian - Iqbal Ali Husni; Afiyah, Novia Nurul; Hanisya Putri Kania Mardika; I Gede Suweda Anggana Putera; Agung Tri Nugroho (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Sodong Beach, Karangbenda Village, Adipala District, Cilacap Regency, serves as a crucial habitat for several sea turtle species, including the olive ridley (Lepidochelys olivacea), green sea turtle (Chelonia mydas), and hawksbill turtle (Eretmochelys imbricata). Unfortunately, this habitat faces significant threats, including plastic pollution, egg poaching, and a general lack of public awareness about conservation. A community service initiative was launched through the “Our Friend Turtles” program, aiming to increase public awareness and concern, particularly among elementary school students. Early childhood education on the importance of turtle conservation has proven to be highly effective in supporting the survival and sustainability of sea turtle populations. The program’s implementation involved socialization and educational activities that covered turtle species, their conservation status, the threats they face, and actionable protection efforts suitable for young children. The initiative also engaged the Nagaraja sea turtle Conservation Group as a key partner, strengthening the involvement of local coastal communities in conservation efforts. The results demonstrate that a science and technology-based approach to socialization and education successfully instilled early awareness among TPQ children in Karangbenda Village about the importance of protecting turtles from both environmental and human threats. This approach also enhanced ongoing conservation efforts and contributed to the creation of a more sustainable and resilient coastal ecosystem. Consequently, the “Our Friend Seaturtles” program has the potential to serve as a practical and sustainable model for conservation education in Cilacap’s coastal areas, promoting long-term environmental stewardship among future generations.